Primary Peripheral Gamma Delta T-Cell Lymphoma of the Central Nervous System: Report of a Case Involving the Intramedullary Spinal Cord and Presenting with Myelopathy - Jeemin Yim; Seung Geun Song; Sehui Kim; Jae Won Choi; Kyu-Chong Lee; Jeong Mo Bae; Yoon Kyung Jeon (Korean Society of Pathologists & the Korean Society for Cytopathology, 2019)
Primary central nervous system lymphoma of T-cell origin (T-PCNSL) is rare, and its clinicopathological features remain unclear. Peripheral T-cell lymphoma of γδ T-cell origin is an aggressive lymphoma mainly involving extranodal sites. Here, we report a case of γδ T-PCNSL involving the intramedullary spinal cord and presenting with paraplegia. A 75-year-old Korean woman visited the hospital complaining of back pain and lower extremity weakness. Magnetic resonance imaging revealed multifocal enhancing intramedullary nodular lesions in the thoracic and lumbar spinal cord. An enhancing nodular lesion was observed in the periventricular white matter of the lateral ventricle in the brain. There were no other abnormalities in systemic organs or skin. Laminectomy and tumor removal were performed. The tumor consisted of monomorphic, medium-to-large atypical lymphocytes with pale-to-eosinophilic cytoplasm. Immunohistochemically, the tumor cells were CD3(+), TCRβF1(-), TCRγ(+), CD30(-), CD4(-), CD8(-), CD56(+), TIA1(+), granzyme B(+), and CD103(+). Epstein-Barr virus in situ was negative. This case represents a unique T-PCNSL of γδ T-cell origin involving the spinal cord.